A diaper bank and home visiting partnership: Initial exploration of research and policy questions. Issue 2 (13th December 2017) - Sadler, Lois S.; Condon, Eileen M.; Deng, Shirley Z.; Ordway, Monica Roosa; Marchesseault, Crista; Miller, Andrea; Alfano, Janet Stolfi; Weir, Alison M.
Abstract: Objectives: The cost of diapering an infant can place a significant financial strain on families living in poverty. Partnerships between diaper banks and home visiting programs for young families may offer an innovative solution to expanding the reach and impact of diaper banks in low‐income communities. The purpose of this pilot study was to uncover preliminary information about the functions of diaper distribution through home visiting programs, and to inform future research and policy questions regarding diaper distribution to families in need. Design and Sample: In this descriptive qualitative pilot study, semi‐structured interviews were conducted with 6 home visitors from Minding the Baby ® (MTB), a home visiting intervention for young parents. MTB clinicians routinely distribute diapers in partnership with The Diaper Bank in Connecticut. We used directed content analysis to code and analyze interview transcripts. Results/Conclusion: These preliminary findings indicate that partnerships between home visiting programs and diaper banks may benefit families by improving diaper access, reducing stigma, and fostering trusting relationships with home visitors. Home visiting program benefits including engagement or re‐engagement with families may need to be balanced with potential effects on clinical and therapeutic relationships. Recommendations for next steps in research and related policy questions are discussed.